Influence of Social Media Usage on the Development of Civic Values and Social Behaviour among Secondary School Students in Zamfara State, Nigeria - Sule Muhamamd; Ibrahim Danda Abubakar (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2026)
This study investigated the influence of social media usage on the development of civic values and social behaviour among secondary school students in Zamfara State, Nigeria. The study was guided by three objectives, three research questions, and three null hypotheses tested at the 0.05 level of significance. A descriptive survey research design was adopted. The population comprised all senior secondary school students in public secondary schools in Zamfara State, while a sample of 375 respondents was selected using a multistage sampling procedure. Data were collected using a researcher-developed instrument titled Social Media Usage, Civic Values and Social Behaviour Questionnaire (SMUCVSBQ). The instrument was validated by experts in Social Studies Education, Educational Psychology, and Measurement and Evaluation, while its reliability was established using Cronbach's Alpha, which yielded a reliability coefficient of 0.86. Mean and standard deviation were used to answer the research questions, whereas Simple Linear Regression Analysis and Pearson Product Moment Correlation were used to test the hypotheses. The findings revealed that social media usage significantly influenced the development of civic values (β = .447, p < .001) and social behaviour (β = .529, p < .001) among secondary school students. The study also established a significant positive relationship between social media usage and overall civic and social development (r = .618, p < .001). The study concluded that responsible social media usage contributes positively to students' civic values and social behaviour. It recommended the integration of digital citizenship education into the school curriculum, promotion of responsible social media use, and strengthened collaboration among schools, parents, and policymakers to maximize the educational and civic benefits of social media.